Durability of Unsupported Pt-Ni Aerogels in PEFC Cathodes. Issue 12 (17th August 2017) - Henning, Sebastian; Herranz, Juan; Ishikawa, Hiroshi; Kim, Bae Jung; Abbott, Daniel; Kühn, Laura; Eychmüller, Alexander; Schmidt, Thomas J.
Abstract : The commercial success of polymer electrolyte fuel cells (PEFCs) depends on the development of Pt-based oxygen reduction reaction (ORR) catalysts with greater activity and stability to reduce the amount of expensive noble metal per device. To advance toward this goal, we have tested a novel class of unsupported bimetallic alloy catalysts (aerogels) as the cathode material in PEFCs under two accelerated stress test conditions and compared it to a state-of-the-art carbon-supported benchmark (Pt/C). The investigated Pt3 Ni aerogel shows little degradation under high potential conditions (> 1.0 V) which can occur during fuel starvation and start-up/shut-down of the cell. If tested under the same conditions, the Pt/C benchmark displays significant losses of electrochemical surface area and ORR activity due to carbon support corrosion as observed in cross section and transmission electron microscopy analysis. When testing the durability upon extended load cycling (0.6–1.0 V), Pt3 Ni aerogel demonstrates less stability than Pt/C which is related to the severe Ni leaching from the alloy under such conditions. These findings highlight the advantages of using unsupported ORR catalysts in PEFCs and point to the reduction of non-noble metal dissolution as the next development step.